Makna Takdir dalam Al-Qur’an: Studi Analisis Tafsir Al-Amthal Fī Tafsīr Kitāb Allah Al-Munzal - Saputra, Nanda; Asyari (Sekolah Tinggi Agama Islam Sadra Jakarta), Hasyim (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The issue of the concept of fate and human freedom in Islamic theology involves various perspectives, such as Qadariyah, which emphasizes human freedom, and Jabariyah, which considers fate as absolute decree. Tafsir Al-Amthal combines these diverse views to provide a comprehensive understanding of the verses of the Qur'an. The research focuses on the views of Nāsir Makārim Shīrāzī in his work